Relationship between the shear modulus of the quadriceps and gastrocnemius muscles and the height of the Drop Jump in basketball athletes - Brandão, M. C. A.; Albuquerque, M.; Oliveira, L. F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Basketball is a complex contact sport that involves multiple jumps, acceleration, deceleration and changes of movement direction. The mechanical properties of the musculotendinous tissue may be important for understanding the prevalent injuries and athletes performance. Elastography is a technique for assessing, in vivo, the shear modulus which is proportional to tissue stiffness, estimated from the propagation velocity of shear waves generated by high-intensity ultrasonic pulses focused at different tissue depths (1). Using another technique, Ando et al. (2) observed a relation between the stiffness of the medial gastrocnemius muscle and the Drop Jump height of non-athlete individuals, after a training period. There seem to be no studies describing this relationship in basketball athletes. This study aimed to correlate the shear modulus (*) of the medial and lateral gastrocnemius, vastus medialis and the distal site of the vastus lateralis muscles with the height obtained in the Drop Jump jump test.